Geochemical Characteristics and Fluid Properties of the Qixia Formation Dolomites of the Middle Permian in the Shuangyushi Block, NW Sichuan Basin, China - Xu, Wenli; Zhou, Gang; Wan, Cixuan; Zhang, Lianjin; Tao, Jiali; Xu, Changhai; Yan, Xue (Frontiers in Earth Science, 2022)
On the basis of petrology, in combination with analysis of the geochemical characteristics of major and trace elements, REE (rare earth elements), carbon isotopes, oxygen isotopes, strontium isotopes and fluid inclusions, the geochemical characteristics and fluid properties of the Qixia Formation dolomites of the Middle Permian Qixiain the Shuangyushi block in the NW Sichuan Basin were systematically studied. The analysis results of the samples show that the Qixia dolomites are mainly composed of medium, coarse, medium-coarse crystalline and dolomites with polymodal crystal size distribution, and cloudy centers and clear rims. They generally show dark purple cathodoluminescence (CL) colors in the centers and orange red CL colors in the rims. The Qixia dolomites are relatively highly ordered (0.79–0.95, averaging 0.90). The CaO and MgO contents show a negative correlation. They are characterized by higher Mg/Ca ratio (0.89–0.92, averaging 0.91), high Fe (94–2,991 ppm, averaging 622 ppm), high Mn (26–185 ppm, averaging 102 ppm), high Na (210–374 ppm, averaging 277 ppm) contents, low Sr (53–218 ppm, averaging 93 ppm) content and lower ∑REE (1.10–5.56 ppm, averaging 2.08 ppm) concentrations. The REE patterns of the dolomites are similar to those of the calcites (C1), and are characterized by light REE (LREE) enrichment, heavy REE (HREE) depletion (LREE/HREE = 5.38–9.58, averaging 7.10), and Eu (0.65–4.19, averaging 1.70) and Ce (0.99–9.52, averaging 2.61) positive anomalies. They have consistent δ13C (1.98–4.27‰ VPDB, averaging 3.01‰ VPDB) and δ18O (−9.54‰–−4.65‰ VPDB, averaging −7.09‰ VPDB) values with the coeval seawater. The salinity index Z is larger than 120, with diagenetic temperature higher than normal temperature. The average value of 87Sr/86Sr is positive (0.707150–0.712273, averaging 0.708669), while some samples are consistent to those of the coeval seawater. Their homogenization temperatures of fluid inclusions (96.3°C–105.0°C, averaging 101.1°C) exceed 100°C, which is equivalent to the buried paleogeothermal temperature, and their salinity (12.3%–14.3%, averaging 13.5%) is 3–5 times that of normal seawater. Based on the regional geological setting and previous research achievements, the dolomitized fluids in the Qixia Formation are probably derived from seawater or marine fluids sealed in pores under shallow-burial environment. The dolomites experienced late alternation by deep high-salinity hydrothermal fluids, and were formed before the Middle-Late Triassic Period.